Comparison of Single-injection and Continuous Femoral Nerve Block after Primary Total Knee Arthroplasty on Postoperative Pain Control and Length of Hospital Stay: A Randomized, Double-blind Study - Tangwiwat, Suwimon (Thai Journal of Anesthesiology, 2021)
Introduction: Effective pain management, including the use of peripheral nerve block (PNB) and multimodal analgesia is important to facilitate and enhance recovery after painful total knee arthroplasty (TKA) surgery. Objective: This study aimed to compare the analgesic efficacy between single-injection (sFNB) and continuous femoral nerve block (cFNB) in patient undergoing TKA within 48 hours. Materials and Methods: This prospective, randomized double-blind study was conducted in 56 elective primary TKA. Patients were allocated to receive either sFNB (n=28) or cFNB (n=28). In sFNB received 0.25% levobupivacaine 30 ml for single injection, while cFNB received 0.1% levobupivacaine 30 ml single injection then infusion 0.08% levobupivacaine 4 ml/hr. The primary outcome was morphine consumption within 48 hours after surgery. The secondary outcomes included postoperative numerical pain score (NRS), PNB-related and opioid-related side effects, patient satisfaction and length of stay (LOS). Results: Demographic data was not statistically different between the two groups. Mean difference postoperative morphine consumption was significantly lower in group cFNB compared to sFNB at 24 hours (MD 8.15 mg; 95% CI=0.60-15.70, p<0.05), and 48 hours (MD 10.33 mg; 95% CI=0.35-20.32, p<0.05). There was no statistical difference in the secondary outcomes. Higher rate of quadriceps weakness occurred significantly more in group cFNB than sFNB (48% vs 3.8%; p<0.05) in the physiotherapist’s documentation while the rate of falls was 3.7% in cFNB. Conclusion: CFNB displayed better analgesia properties compared to a single-injection FNB after TKA, however, the perineural technique was associated with higher rate of quadriceps muscle weakness and increased risk of falls